2012
DOI: 10.1039/c2an16223g
|View full text |Cite
|
Sign up to set email alerts
|

Direct ionization of biological tissue for mass spectrometric analysis

Abstract: Analysis of biological tissue at a molecular level is of great importance in biological, medical and clinical studies. In this manuscript, we report that both plant and animal tissues can be directly ionized and analyzed by mass spectrometry under ambient conditions. By adding some solvents and applying a high voltage, spray ionization can be induced at the tip of biological tissue and a mass spectrum can be observed. Various plant and animal tissues have been tested and compounds such as lipids, alkaloids, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 44 publications
6
78
0
3
Order By: Relevance
“…For comparison, the extract was directly analyzed with the extract solution loaded to the sharp tip-end of the wooden tips. Both polar and low-polar compounds and compounds such as monogalactosyl diacylglycerol (MGDG) and digalactosyl diacylglycerol (DGDG) were detected in this case (Figure 2c), covering most components observed by LC-MS [15]. These components, however, could not be detected by analysis of the extract using nano-ESI [15].…”
Section: Separation Property Of Wooden Tipsmentioning
confidence: 90%
See 4 more Smart Citations
“…For comparison, the extract was directly analyzed with the extract solution loaded to the sharp tip-end of the wooden tips. Both polar and low-polar compounds and compounds such as monogalactosyl diacylglycerol (MGDG) and digalactosyl diacylglycerol (DGDG) were detected in this case (Figure 2c), covering most components observed by LC-MS [15]. These components, however, could not be detected by analysis of the extract using nano-ESI [15].…”
Section: Separation Property Of Wooden Tipsmentioning
confidence: 90%
“…Both polar and low-polar compounds and compounds such as monogalactosyl diacylglycerol (MGDG) and digalactosyl diacylglycerol (DGDG) were detected in this case (Figure 2c), covering most components observed by LC-MS [15]. These components, however, could not be detected by analysis of the extract using nano-ESI [15]. These results indicated that the solid-substrate ESI had lower signal suppression and could provide a more complete profile of the sample.…”
Section: Separation Property Of Wooden Tipsmentioning
confidence: 91%
See 3 more Smart Citations